2021
DOI: 10.3390/bios11030079
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Imprinted Polymer-Quantum Dot Materials in Optical Sensors: An Overview of Their Synthesis and Applications

Abstract: In the last decades analytical methods have focused on the determination of target analytes at very low concentration levels. This has been accomplished through the use of traditional analytical methods that usually require high reagent consumption, expensive equipment and long pretreatment steps. Thus, there is a demand for simple, rapid, highly selective and user-friendly detection procedures. Quantum dots (QDs) are semiconductor fluorescent nanomaterials with unique optoelectronic properties that have shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 59 publications
(136 reference statements)
0
17
0
Order By: Relevance
“…Optical biosensors with increased stability, sensitivity and selective fluorescence response could be constructed by integrated surface imprinted polymers with QDs. 60,61,88,89 For the first time, Tang et al 90 demonstrated the validity of the combination of CdS QDs and MIT to synthesize BSA-surface imprinted polymers for target protein recognition. The CdS QDs not only provided large specific surface areas, which were beneficial to high binding capacity but also were responsive to the binding with a template, which led to the quenching of the photoluminescence emission of CdS QDs.…”
Section: Traditional Imprinting Methodsmentioning
confidence: 99%
“…Optical biosensors with increased stability, sensitivity and selective fluorescence response could be constructed by integrated surface imprinted polymers with QDs. 60,61,88,89 For the first time, Tang et al 90 demonstrated the validity of the combination of CdS QDs and MIT to synthesize BSA-surface imprinted polymers for target protein recognition. The CdS QDs not only provided large specific surface areas, which were beneficial to high binding capacity but also were responsive to the binding with a template, which led to the quenching of the photoluminescence emission of CdS QDs.…”
Section: Traditional Imprinting Methodsmentioning
confidence: 99%
“…The fluorescence sensors have become the most common optical technique due to their low detection limitations and format simplicity. Since the quenching phenomenon occurs in the presence of sample components and some materials (analytes), QD-based probes have low selectivity, based on the existing reports [ 56 ]. Fluorescence-based optical sensors have excellent performance in detecting viruses due to the availability of commercial fluorescent probes and advanced optical elements.…”
Section: Qd-based Nanobiosensorsmentioning
confidence: 99%
“…After the polymerization reaction, the target molecule is extracted leaving a specific imprint on the polymer. With the resulting MIP-QD composite, the measured quenching effect during the recognition events in the evaluated target solutions allows to quantify the analyte concentration [37]. The different quenching mechanisms and a series of examples are nicely reviewed in references [38,39].…”
Section: Imprinted Polymer -Quantum Dots (Qds)mentioning
confidence: 99%